Boric acid-functionalized PANI-ABA/PA hydrogel-based flexible pH sensor for real-time sweat monitoring - Gao, Meihui; Zhang, Xianjing; Li, Shiqi; Gao, He; Li, Xinyu; Xu, Dongyuan; Xu, Longbin (Analytica chimica acta, 2025)
Wearable pH sensors have emerged as promising tools for real-time health monitoring, particularly for sports and clinical applications, due to their ability to monitor key physiological indicators such as sweat pH. Sweat analysis provides valuable insights into metabolic processes and physical exertion. However, the development of flexible, stable, and highly sensitive sensors for accurate sweat pH detection remains a challenge. Conductive polymer such as polyaniline (PANI), have gained attention due to their unique properties, but further improvements in mechanical flexibility and sensor performance are needed to fully realize their potential for wearable biosensing applications. We present a boric acid-functionalized PANI-ABA/PA hydrogel, synthesized via electrochemical deposition, where boric acid plays a crucial role in crosslinking the rigid PANI material into a flexible, porous grid structure. This crosslinking improves the mechanical properties of the hydrogel while enhancing its ion-exchange capacity, leading to greater sensitivity and selectivity for H+ ions. PANI-ABA/PA hydrogel exhibits super-Nernstian behavior (77.80 mV pH−1) across the physiological pH range (3.00–10.00), with rapid response times, minimal temperature drift, and excellent repeatability. Moreover, the hydrogel exhibits outstanding antifouling properties, ensuring consistent performance even in dynamic environments. Real-time human subject testing confirms the sensor's ability to accurately monitor sweat pH during physical activity, providing reliable and real-time data. These results highlight the promising potential of the PANI-based hydrogel for wearable biosensors in health monitoring. This study highlights the role of boric acid in facilitating the formation of a crosslinked PANI-based grid structure, which improves the sensor's performance in wearable applications. Enhanced sensitivity, stability, and mechanical flexibility make this smart wearable sensor a promising candidate for continuous, non-invasive health monitoring. It opens new opportunities for real-time athletic performance tracking, personalized healthcare, and disease diagnostics, positioning it as a leading technology for future wearable health-monitoring systems. [Display omitted] •A boric acid-functionalized PANI-ABA/PA hydrogel were prepared successfully.•PANI-ABA/PA demonstrates detection performances for wearable use.•Wearable sweat pH sensing based on the PANI-ABA/PA hydrogel.